Perturbation of nucleo‐cytoplasmic transport affects size of nucleus and nucleolus in human cells. Issue 5 (25th February 2016) - Ganguly, Abira; Bhattacharjee, Chumki; Bhave, Madhura; Kailaje, Vaishali; Jain, Bhawik K.; Sengupta, Isha; Rangarajan, Annapoorni; Bhattacharyya, Dibyendu
Abstract : Size regulation of human cell nucleus and nucleolus are poorly understood subjects. 3D reconstruction of live image shows that the karyoplasmic ratio (KR) increases by 30–80% in transformed cell lines compared to their immortalized counterpart. The attenuation of nucleo‐cytoplasmic transport causes the KR value to increase by 30–50% in immortalized cell lines. Nucleolus volumes are significantly increased in transformed cell lines and the attenuation of nucleo‐cytoplasmic transport causes a significant increase in the nucleolus volume of immortalized cell lines. A cytosol and nuclear fraction swapping experiment emphasizes the potential role of unknown cytosolic factors in nuclear and nucleolar size regulation. Abstract :